Nutritional supplementation of the pharmacotherapy of prostate diseases - Oleg I. Bratchikov; Igor A. Tyuzikov; Pavel A. Dubonos (Belgorod National Research University, 2021)
Introduction: Nutritional supplementation is an integral part of modern pharmacotherapeutic strategies for prostate diseases with different levels of evidence for specific nutrients. Provitamin A (beta-carotene), vitamin A (retinol) and prostate diseases. Their effects have not been sufficiently studied, and the available data are conflicting to recommend them as a nutritional supplement. Vitamin E (tocopherol) and prostate diseases. Its effects have not been sufficiently studied, and the available data are conflicting to recommend it as a nutritional supplement. Vitamin C (ascorbic acid) and prostate diseases. Its effects have not been sufficiently studied, and the available data are conflicted to recommend it as a nutritional supplement. Vitamin K and prostate diseases. Its effects have not been sufficiently studied, and the available data are conflicted to recommend it as a nutritional supplement. Vitamin D and prostate diseases. The evidence base of the vitamin D prostatotropic effects has been accumulated, which allows us to consider its deficiency replacement as an effective nutritional supplement in prostate diseases. Omega-3 PUFAs and prostate diseases. They have universal physiological effects; however, the evidence base for their recommendation as a nutritional supplement for prostate diseases is still insufficient. Zinc and prostate diseases. Positive effects of zinc on the prostate gland are known for a fact and allow us to recommend it as a nutritional supplement for prostate diseases. Selenium and prostate diseases. The reliably proven positive effects of selenium on the prostate gland allow us to recommend it as a nutritional supplement for prostate diseases. Magnesium and prostate diseases. Its effects have not been sufficiently studied, and the available data are conflicting to recommend it as a nutritional supplement.